PERBAIKAN PEMBELAJARAN DENGAN MENGGUNAKAN BUPENA PADA PERCOBAAN TEMA BAGIAN TUMBUH-TUMBUHAN DAN FUNGSINYA DI KELAS IV SD NEGERI 068007 MEDAN TUNTUNGAN - Hotma Tiolina Siregar; Taty Sukanti Halawa (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2021)
This study aims to improve science learning by using BUPENA which has been developed in the Experimental Theme of Plants and Their Functions. The subjects in this study were students of SD NEGERI 068007 Medan Tuntungan TP.2020-2021, with the object of improving the lesson plans and the use of Bupena. This research uses Classroom Action Research with 2 cycles of improvement. The results showed that there was an improvement in learning, this can be seen from the suitability of the lesson plans that were prepared with the aim and the increase in the score on the teaching simulation video observation instrument in cycle 1 learning obtained a score of 90, after conducting learning simulations and conducting experiments the score increased by 96. The results of the study obtained that the N-Gain score of Learning Improvement in cycle 1 was 90 and 96 in cycle 2. Thus it can be concluded that there was an improvement in science learning using Bupena in the experimental theme Part of plants and their functions in Class IV SD 068007 Medan Tuntungan TP.2020 -2021.Keywords: Right, Bupena, Temptation